2015
DOI: 10.1038/srep18197
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between Three Gorges Dam impacts and the dramatic recessions in China’s largest freshwater lake, Poyang Lake

Abstract: Despite comprising a small portion of the earth’s surface, lakes are vitally important for global ecosystem cycling. However, lake systems worldwide are extremely fragile, and many are shrinking due to changing climate and anthropogenic activities. Here, we show that Poyang Lake, the largest freshwater lake in China, has experienced a dramatic and prolonged recession, which began in late September of 2003. We further demonstrate that abnormally low levels appear during October, 28 days ahead of the normal init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 34 publications
2
77
1
Order By: Relevance
“…The mutiple forces by precipitation, inflow, the air temperature and evaporation resulted in a decline in water levels in Lake Superior in North America at the rate of approximately 1.0 cm per year [31]. The water level variation of Poyang Lake in China may be a combination effect by the operation of TGR [64], serious sand mining and waterway regulation [65]; The precipitation in the Huai River basin decreased since the mid-1960s, while the WLM increased significantly. WLM of Hongze Lake has been changed more and more by anthropogenic activities (especially hydraulic engineering) from 1950s [29].…”
Section: Further Evaluation On the Hydrological Variation Linked To Amentioning
confidence: 99%
“…The mutiple forces by precipitation, inflow, the air temperature and evaporation resulted in a decline in water levels in Lake Superior in North America at the rate of approximately 1.0 cm per year [31]. The water level variation of Poyang Lake in China may be a combination effect by the operation of TGR [64], serious sand mining and waterway regulation [65]; The precipitation in the Huai River basin decreased since the mid-1960s, while the WLM increased significantly. WLM of Hongze Lake has been changed more and more by anthropogenic activities (especially hydraulic engineering) from 1950s [29].…”
Section: Further Evaluation On the Hydrological Variation Linked To Amentioning
confidence: 99%
“…The anthropogenic activities mainly include dam and reservoir construction, water withdraw, land use, and land cover changes, along with sand extraction from river and lake beds. Mei et al argued that the average contributions of precipitation variation, human activities in the Poyang Lake catchment, and the Three Gorges Reservoir regulation to the Poyang Lake recession can be quantified as 39.1%, 4.6% and 56.3%, respectively [31]. Zhang et al found that human-induced and climate-induced influences on streamflows are different in the five Poyang Lake sub-basins.…”
Section: Discussion On Temporal Changes In Streamflow and Water Levelmentioning
confidence: 99%
“…Ye et al [65] indicated that the Yangtze River discharge has a greater impact on the annual lake level variation than the lake's catchment inflow and that the advance of the Poyang Lake dry season has been primarily driven by climate change in the Yangtze River Basin since the 1990s and was further aggravated by the Three Gorges Dam in the 2000s. Mei et al [66] quantified the average contributions of the regulation of the Three Gorges Dam, precipitation changes, and human activities in the Poyang Lake Basin to the water level reduction in Poyang Lake as 56.3%, 39.1%, and 4.6%, respectively. In addition to the comprehensive effects of the five rivers, the Yangtze River, and water conservancy projects, there are some other factors that affect the lake's water level.…”
Section: Analysis Of the Driving Forces Of The Poyang Lake Drynessmentioning
confidence: 99%
“…In addition, large amounts of sand extraction in Poyang Lake since 2003 have resulted in variations in the lake terrain and caused the outflow channel of the lake to become wider and deeper, thus allowing the lake to drain quickly and reach a lower water level [68]. However, Mei et al [66] argued that the contribution of sand extraction to the reduction of the lake's water level since 2000 may be overestimated. In addition, Ye et al [65] also argued that the specific effects of changes in lake terrain conditions on the lake's water level require further study.…”
Section: Analysis Of the Driving Forces Of The Poyang Lake Drynessmentioning
confidence: 99%